(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
We present the micropaleontological record on ongoing research on Paleogene larger foraminifers from Central Italy collected in the field work for the realization of the geological sheet 348 “Antrodoco” of the Geological Map of Italy 1:50.000 scale. The work provides an examination of the biostratigraphic potential of selected taxa with emphasis on rotaliids. Ornatorotalia is documented for the first time from the Paleocene. Possible new species of Miscellanea, Ornatorotalia, and Rotalia are figured and described in open nomenclature.